Intra-patient comparison of parietal pleural biopsies by rigid forceps, flexible forceps and cryoprobe obtained during medical thoracoscopy: a prospective series of 80 cases with pleural effusion - Wurps, H. (BMC Pulm Med, 2016)
BACKGROUND: There is only few data available on the use of cryotechnique during medical thoracoscopy. METHODS: Medical thoracoscopy was performed in consecutive patients with pleural effusion. Prospectively, biopsies were taken by rigid forceps, flexible forceps and cryoprobe. Specimen size, depth and diagnostic yield were compared. RESULTS: 80 Patients were included. 408 biopsies were taken (205 rigid biopsies, 104 flexible biopsies, 99 cryobiopsies). Mean surface area of rigid biopsies was 22.6 ± 20.4 mm(2) (flexible biopsies: 7.1 ± 9.3 mm(2), cryobiopsies: 14.4 ± 12.8 mm(2)). Rigid biopsies were significantly larger than cryobiopsies (p < 0.001) and flexible biopsies (p < 0.001), crybiopsies were significantly larger than flexible biopsies (p < 0.01). A deep biopsy containing fatty tissue was harvested in 63 % of rigid biopsies (cryobiopsy: 49.5 % flexible biopsy: 39.5 %). In 79/80 cases (98.7 % 95 % CI cannot be calculated) a diagnosis was obtained by rigid biopsy (cryobiopsy: 73/80 cases (91.3 % 95 % CI 86.0 – 96.5 %), flexible biopsy: 74/80 cases (92.5 % 95 % CI 88.6 – 97.4 %)). Diagnostic yield achieved with cryobiopsies was inferior to the yield of rigid biopsies (Difference: 12.7 %), but non-inferior to flexible biopsies (Difference: 6.5 %). CONCLUSION: Cryobiopsies in medical thoracoscopy are safe with high diagnostic yield, non-inferior to flexible biopsies with increased tissue quantity and quality. Cryotechnique can develop an important role in medical thoracoscopy in the near future when rigid thoracoscopy is not available.